PENDEKATAN DIAGNOSIS DAN TATA LAKSANA MULTIDISIPLIN JANGKA PANJANG PADA NEUROPATI HEREDITER: CHARCOT MARIE TOOTH - Putri Widya Andini; Manfaluthy Hakim; Fitri Octaviana; Luh Ari Indrawati; Winnugroho Wiratman; Triana Ayuningtyas; Ahmad Yanuar Safri (NEURONA, 2020)
Hereditary neuropathy is the most common inherited neuromuscular diseases, with Charcot Marie Tooth being the most common form. It is characterised by degeneration of peripheral sensory and motor nerves due to axonal degeneration or demyelination. The diagnosis of hereditary neuropathy requires comprehensive history taking including family history to determine the mode of inheritance, clinical and neurophysiological examination, and genetic testing. This review provides a diagnostic approach and long-term multidisciplinary management in patients with suspected hereditary neuropathy. Keywords: Charcot Marie Tooth, genetics, neuropathy